Interaksi Belajar Kelas Bahasa Indonesia: Sebuah Tinjauan Konseptual - Dika Zakiyah; Mutiara Widya Utami; Wahyuni Shofinna Nur; Ajat Manjato (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research presents the basic concept of learning interaction, especially in the Indonesian classroom. A literature review is a technique used in this study. The data collection technique was carried out by searching for library sources based on the outline topic, grouping library sources based on relevance to the subject and year of the research, then sequencing the structure of explanations and comparing interrelated data. The data is then analyzed through 3 steps, namely data reduction, data presentation, and verification. The results of the study explained that in general the interaction is divided into three patterns, (1) one-way patterns, (2) two-way patterns, and (3) multi-directional patterns. All three are needed in the learning process. However, what should be more dominant is the multi-directional pattern. In language classes, especially Indonesian interactions, learning interaction aims to develop four aspects of language skills, namely (1) listening, (2) speaking, (3) reading and (4) writing. Each aspect of skill has its pattern, technique/method. In addition, teacher and student activities during learning can be classified into seven categories of interactions known as the Brown Interaction Analysis System (BIAS).